Towards an Integrated, Liberal Theory of the Canadian State - O’Byrne, Shannon (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1992)
In this article, the author challenges the tendency in common law Canada to conflate the distinction between State and society. Following the analysis of Kenneth Dyson, the author contends that the State occupies a distinct sphere produced by or contained in the interconstitutive relationship of State institution, on the one hand, and State idea, on the other. The State concept is presented as neither merely active nor merely passive but as involving a relationship between action and reflection, between institution and idea. The author then analyses the broadly shared public values which are contained in the Canadian State idea when viewedfrom a liberal political perspective. That these values incrementally modulate the exercise of public power — and vice versa — argues for a State-society distinction which is not generally emphasized in common law Canada.